Orf virus DNA prime-protein boost strategy is superior to adenovirus-based vaccination in mice and sheep - Wang, Yan; Sun, Shihui; Zhao, Kui; Du, Le; Wang, Xinyue; He, Wenqi; Gao, Feng; Song, Deguang; Guan, Jiyu (Frontiers in Immunology, 2023)
Contagious ecthyma (Orf), an acute and highly contagious zoonosis, is prevalent all over the world. Orf is caused by Orf virus (ORFV), which mainly infects sheep/goats and human beings. Therefore, effective and safe vaccination strategies for Orf prevention are needed. Although immunization with single-type Orf vaccines have been tested, heterologous prime-boost strategies are still needed to be studied. In the present study, ORFV B2L and F1L were selected as immunogens, based on which DNA, subunit and adenovirus vaccine candidates were generated. Of note, heterologous immunization strategies using DNA prime-protein boost and DNA prime-adenovirus boost in mice were performed, with single-type vaccine as controls. We have found that the DNA prime-protein boost strategy induces stronger humoral and cellular immune responses than DNA prime-adenovirus boost strategy in mice, which was confirmed by the changes of specific antibodies, lymphocyte proliferation and cytokine expression. Importantly, this observation has also been confirmed when these heterologous immunization strategies were performed in sheep. In summary, by comparing the two immune strategies, we found that DNA prime-protein boost strategy can induce better immune response, which provide new attempt for the exploration of Orf immunization strategy.